Diversity Patterns of Spontaneous Plants and Their Multi-Scale Driving Mechanisms in Cold Regions: A Case of 14 Cities in Heilongjiang Province, China - Feinuo Li; Congcong Zhao; Haiyan Zhu; Xueting Yang; Yuandong Hu (Plants, 2025)
Cold-climate cities remain poorly studied, yet their spontaneous flora is strongly shaped by severe winters and short growing seasons. Heilongjiang Province, the northernmost region of China, provides a valuable case study given its rapid urbanization. As an important component of urban biodiversity, the diversity distribution patterns of spontaneous plants and their underlying causes remain underexplored from multi-scale and multi-dimensional perspectives. Therefore, this study aimed to test how climatic subzones and habitat types jointly influence spontaneous plant diversity across urban landscapes in 14 cities of Heilongjiang Province. Based on vegetation surveys, we applied calculations of α- and β-diversity, along with hierarchical clustering, across climatic subzones, cities, and habitat types to elucidate the diversity patterns and their multi-scale driving mechanisms. The results showed the following: (1) A total of 778 spontaneous plant species were recorded, belonging to 98 families and 395 genera. Native plants accounted for 58.7%, and non-native plants accounted for 41.3% (including 77 invasive species). (2) Perennial herbs dominated overall (45.2%), consistent with winter filtering, whereas annual/biennial herbs were more common in warmer subzones such as II B2. (3) Forest gaps (FG) and shrub–grassland gaps (SG) supported the most diverse spontaneous plant communities, highlighting habitat heterogeneity. (4) Species richness peaked in subzone II B2 and was lowest in subzone I A1, while abandoned land (SA) and shrub–grassland gaps (SG) supported the richest communities. (5) β-diversity analyses indicated homogenization under extreme cold in subzone I A1 and greater turnover in warmer subzone II B2, reflecting contrasting climatic filters. The “light patches” in FG habitats and the “disturbance filtering” in LA habitats further shaped the differences in local communities. This study reveals the diversity distribution patterns and adaptation strategies of spontaneous plants in cold cities, emphasizing their integration into urban planning while addressing the dominance of invasive species.